Förster resonance energy transfer-based kinase mutation phenotyping reveals an aberrant facilitation of Ca2+/calmodulin-dependent CaMKIIα activity in de novo mutations related to intellectual disability - Fujii, Hajime; Kidokoro, Hiroyuki; Kondo, Yayoi; Kawaguchi, Masahiro; Horigane, Shin-ichiro; Natsume, Jun; Takemoto-Kimura, Sayaka; Bito, Haruhiko (Frontiers in Molecular Neuroscience, 2022)
CaMKIIalpha plays fundamental roles in learning and memory and is a key determinant of synaptic plasticity. Its kinase activity is regulated by binding of Ca2+/CaM and by autophosphorylation that operates in an activity-dependent manner. Though many mutations in CAMK2A were linked to a variety of neurological disorders, the multiplicity of its functional substrates renders a systematic molecular phenotyping challenging. In this study, we report a new case of CAMK2A P212L, a recurrent mutation, in a patient with intellectual disability. To quantify the effect of this mutation, we developed a FRET-based kinase phenotyping strategy and measured aberrance in Ca2+/CaM-dependent activation dynamics in vitro and in synaptically connected neurons. CaMKIIalpha P212L revealed a significantly facilitated Ca2+/CaM-dependent activation in vitro. Consistently, this mutant showed faster activation and more delayed inactivation in neurons. More prolonged kinase activation was also accompanied by a leftward shift in the CaMKIIalpha input frequency tuning curve. In keeping with this, molecular phenotyping of other reported CAMK2A de novo mutations linked to intellectual disability revealed aberrant facilitation of Ca2+/CaM-dependent activation of CaMKIIalpha in most cases. Finally, pharmacological reversal of CAMK2A P212L phenotype in neurons was demonstrated using an FDA-approved NMDA receptor antagonist memantine, providing a basis for targeted therapeutics in CAMK2A-linked intellectual disability. Taken together, FRET-based kinase mutation phenotyping sheds light on the biological impact of CAMK2A mutations and provides a selective, sensitive, quantitative, and scalable strategy for gaining novel insights into the molecular etiology of intellectual disability.